Sociopreneurial behaviour formation: antecedents and conversion. Case of dairy farming industry in Indonesia - Arrasyid, Muhammad Iqbal; Sidek, Shafie; Ismail, Noor Azlin; Amaliyah, Amaliyah (Emerald Publishing, 2024)
Purpose: This study aims to identify the psychological factors predicting sociopreneurial intention (SEI) and gain insight into the conversion of SEI to sociopreneurial behaviour (SEB) in the presence of facilitating events (FE) as a moderating factor. Design/methodology/approach: Hypotheses are statistically tested using a partial least square structural equation modelling (PLS-SEM) based on purposive survey data (n = 110) from the leaders of dairy cooperatives in Indonesia. The measurement items are specifically developed for this research after thoroughly analysing the questionnaire items provided by prior studies. Findings: The findings support the hypotheses that empathy (EM), perceived social responsibility (PSR) and self-efficacy (SEFF) are strong predictors of SEI. Moreover, although SEI can be directly converted to SEB, FE significantly moderated that conversion. Research limitations/implications: Future research should also involve the impact of SEB on the community and the sociopreneurs. Originality/value: This research empirically examines the influence of external factors in converting SEI into SEB, which prior studies overlooked. Moreover, it involves the leaders of dairy cooperatives in Indonesia who perform SEB to help smallholder farmers’ communities facing dairy farming issues such as capital, milk productivity, land size and others as research participants.